Asymmetric Labor Supply Responses to Taxation - Anna Esslinger; Katharina Pfeil; Lars P. Feld (CESifo GmbH, 2024)
Are the effects of tax aversion on labor supply symmetric? In a real-effort online experiment, participants are exposed to manipulated wages and taxes after first experiencing the same reference wage. More participants change their labor supply when encountering a tax increase than when experiencing an equivalent wage decrease. However, there is no significant difference in labor supply change between the groups that received tax decreases and wage increases. Tax averse behavior existing only in the presence of net wage decreases implies asymmetric labor supply responses to taxation.
Keywords: H20; H30; D91; J22; 330; tax aversion; loss aversion; labor supply asymmetry; online experiment